2015
DOI: 10.1111/1467-9604.12091
|View full text |Cite
|
Sign up to set email alerts
|

Culture and poverty: a case study of a girl with special educational needs from a poor community in South India

Abstract: Girls with disabilities from lower economic homes are disadvantaged (in terms of gender, disability and poverty) in India, and are often regarded as useless by their communities. There is a need to improve and provide a chance for self-sufficiency among women with disabilities in India.The purpose of this study was to examine the life-chances (i.e. the likelihood of living a self-sufficient life) of girls with disabilities in rural India and subsequently suggest ways through which one can improve these life ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Don et al (2015) found that girls with disabilities in rural Iran were not expected to work, so parents believed that it was unnecessary to send them to schools. Similarly, another case study conducted in rural India found that parents played down the importance of education for daughters with disabilities and viewed the ideal future in marrying them out (Philip, 2015). Thus, girls with disabilities were more likely to be out of school compared with boys with disabilities and girls without disabilities (Malik et al, 2022).…”
Section: Discrimination Against the Child Within The Familymentioning
confidence: 96%
See 2 more Smart Citations
“…Don et al (2015) found that girls with disabilities in rural Iran were not expected to work, so parents believed that it was unnecessary to send them to schools. Similarly, another case study conducted in rural India found that parents played down the importance of education for daughters with disabilities and viewed the ideal future in marrying them out (Philip, 2015). Thus, girls with disabilities were more likely to be out of school compared with boys with disabilities and girls without disabilities (Malik et al, 2022).…”
Section: Discrimination Against the Child Within The Familymentioning
confidence: 96%
“…showing that it greatly affected the mental health of both the children and their caregivers-generating distress and low self-esteem, leading to their social exclusion and isolation (Ngo et al, 2013;Philip, 2015;Shang & Fisher, 2014;Sukmak & Sangsuk, 2018). Family members, particularly caregivers, most of whom are mothers, also experienced discrimination daily within the community.…”
Section: Stigmatization Of Both Disabled Children and Their Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of teachers who have undertaken the course in Bangalore have been successful in having papers based upon their work accepted for publication (Philip 2015;Haridarshan 2015;Vellal 2015). Such a step requires considerable confidence on the part of teachers who have not previously ventured into the domain of academic publication.…”
Section: Learning From Success Storiesmentioning
confidence: 99%
“…Poverty alone creates issues of education access, and a lack of hygiene facilities exacerbates this (Grinberg, 2010; Philip, 2015). While men may relieve themselves out in the open, in many cultures, modesty dictates that women and girls use filthy, uncleaned pit latrines, which can have detrimental health consequences (Hannan and Andersson, 2002).…”
Section: Review Of the Literaturementioning
confidence: 99%